A review on abrasive water jet machining process and its process parameters. (2020) - Kale, Anusha; S.K., Singh; N., Sateesh; Subbiah, Ram
Abstract: Abrasive water jet machining process is a Non-conventional machining process which has been utilized in mechanical applications. In this project effort has been made to optimize machining parameters utilized during cutting on Hastelloy by utilizing Abrasive Water Jet Machining. The process parameters, for example, transverse speed, stand off-distance, water pressure, Abrasive flow rate. Material Removal Rate and surface roughness are estimated. Taguchi and Grey-Relational Analysis is opted because of multi response Optimization. L27 Orthogonal array is used to conduct Experimentation. To identify the significance of parameters on measured responses, the analysis of variance (ANOVA) has been done.